Los sindicatos obreros y la revolución social / Pierre Besnard ; versión Española de Felipe Aláiz ; [preliminares, J. Peiró] - Aláiz, Felipe (1887-1959); Besnard, Pierre (1886-1947)
Incluye retrato del autor